Ultrastructural studies of ALS mitochondria connect altered function and permeability with defects of mitophagy and mitochondriogenesis - Ruffoli, Riccardo; Bartalucci, Alessia; Frati, Alessandro; Fornai, Francesco (Frontiers in Cellular Neuroscience, 2015)
The key role of mitochondria in patients affected by amyotrophic lateral sclerosis (ALS) is well documented by electron microscopy studies of motor neurons within spinal cord and brainstem. Nonetheless, recent studies challenged the role of mitochondria placed within the cell body of motor neuron. In fact, it was demonstrated that, despite preservation of mitochondria placed within this compartment, there is no increase in the lifespan of transgenic mouse models of ALS. Thus, the present mini-review comments on morphological findings of mitochondrial alterations in ALS patients in connection with novel findings about mitochondrial dynamics within various compartments of motor neurons. The latter issue was recently investigated in relationship with altered calcium homeostasis and autophagy, which affect mitochondria in ALS. In fact, it was recently indicated that a pathological mitophagy, mitochondriogenesis and calcium homeostasis produce different ultrastructural effects within specific regions of motor neurons. This might explain why specific compartments of motor neurons possess different thresholds to mitochondrial damage. In particular, it appears that motor axons represent the most sensitive compartment which undergoes the earliest and most severe alterations in the course of ALS. It is now evident that altered calcium buffering is compartment-dependent, as well as mitophagy and mitochondriogenesis. On the other hand, mitochondrial homeostasis strongly relies on calcium handling, the removal of altered mitochondria through the autophagy flux (mitophagy) and the biogenesis of novel mitochondria (mitochondriogenesis). Thus, recent findings related to altered calcium storage and impaired autophagy flux in ALS may help to understand the occurrence of mitochondrial alterations as a hallmark in ALS patients. At the same time, the compartmentalization of such dysfunctions may be explained considering the compartments of calcium dynamics and autophagy flux within motor neurons. .